2014
DOI: 10.1093/ejo/cju047
|View full text |Cite
|
Sign up to set email alerts
|

The impact of orthodontic treatment on quality of life and self-esteem in adult patients

Abstract: Undergoing fixed orthodontic therapy had a negative impact on the overall OHRQoL, during the first 3 months of treatment, which then improved to pre-treatment scores, whilst a significant increase was observed in self-esteem as a result of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 18 publications
7
84
0
5
Order By: Relevance
“…Our findings demonstrated a minor association with increased overjet, but no association with cross‐bite/scissor‐bite or increased overbite/open bite and the overall OHRQoL. While previous studies have found a significant association between malocclusion and OHRQoL in adults, it should be noted that most of these studies were performed in clinical settings and patient samples included people with both a severe malocclusion and an existing perceived need for treatment. In contrast, this study measuring the relationship between OHRQoL and malocclusion was assessed using a representative population sample in an adult population.…”
Section: Discussionmentioning
confidence: 73%
“…Our findings demonstrated a minor association with increased overjet, but no association with cross‐bite/scissor‐bite or increased overbite/open bite and the overall OHRQoL. While previous studies have found a significant association between malocclusion and OHRQoL in adults, it should be noted that most of these studies were performed in clinical settings and patient samples included people with both a severe malocclusion and an existing perceived need for treatment. In contrast, this study measuring the relationship between OHRQoL and malocclusion was assessed using a representative population sample in an adult population.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, it is questionable whether a clinician can alter or increase a patient's self-esteem by improving his or her dental and facial esthetics, although some studies suggest that orthodontic treatment does improve self-esteem. 35 The characteristics that could improve selfesteem remain to be evaluated in future research. The limitations of this study were a relatively small sample, the inclusion of no young adults who were not students, and the focus only on major craniodentofacial characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3. Descriptive and comparative statistics of the overall self-esteem scores in the test group at baseline (T0), 1-(T1), 3-(T2), and 6-months (T3) and post-treatment (T4; n = 61) [9].…”
Section: Resultsmentioning
confidence: 99%